COMPARATIVE ANALYSIS BETWEEN THE PERFORMANCE PUBLIC AND PRIVATE SCHOOL STUDENT - suman, Manju (International Journal of Multidisciplinary Research and Studies, 2020)
When parents are able to actively encourage their children's healthy growth and development, children flourish. We receive crucial emotional, social, financial, and other forms of support from our families. Parents are the first and most crucial teachers in every child's life. Families provide the environment in which children develop necessary skills, such as decision-making, responsibility, respect for others, expressing affection and receiving love, fulfilling social roles, and expressing creativity. Family is crucial from the moment of birth and is always important. The fourth type of parenting is characterized by low demand and low responsiveness, which results in neglect. These parents don't have strict rules or high expectations. This kind of parent is unfriendly, lacks parental control over their kids, and interacts with them less. They also don't become engaged in kid-related issues and don't pay attention to their kids' needs. They are uninterested in their children's life and insensitive to their needs. These parents typically do not want their children to interrupt them and seldom ask their children's opinions while making choices.